PERBAIKAN DAYA ANTAGONIS TRICHODERMA HARZIANUM RIFAI TERHADAP SEPTOBASIDIUM Spp. MELALUI SINAR UV - SUSWANTO, IMAN; RAMADHAN, TRIS HARIS (Jurnal Agroteknos, 2014)
Currently velvet blight Septobasidium spp. is a major disease of pepper in West Kalimantan. Some control efforts have been made despite lack of satisfactory results. This study aimed to obtain mutant isolates of Trichoderma harzianum which can suppress velvet blight. Mutation was done by UV radiation from the UV-C lamp 15 watt, at range 3-21 minutes exposure series with an interval of 3 minutes. The research results showed that exposure to T. harzianum for 6-9 mins resulted in quicker life cycle of the mutant isolates and still maintain antagonistic properties against Septobasidium spp. UV exposure to T. harzianum more than 18 minutes caused disruption of mycelium growth and sporulation